The Influence of Supervisor Support and Work Environment on Job Performance Through Employee Engagement in The Wood Production Industry in East Kalimantan - Saragih Saragih; Andre Michael; Tuty Lindawati (Jurnal Indonesia Sosial Teknologi, 2024)
Employees or human resources have an essential and large share in the company. The company also realizes that job satisfaction and employee welfare are vital to the company's business activities. With job satisfaction and welfare owned by employees, the company gets feedback such as maximum performance and profits. This study aims to determine whether there is a significant influence of supervisor support and work environment on job performance through employee engagement in the Wood Production Industry in East Kalimantan. The type of data used is quantitative data, with primary data as the source of data in this study. The primary data used is a questionnaire by distributing a google form. The data obtained amounted to 200 respondents. The data analysis technique used in this study is SEM (Structural Equation Modelling) and uses SEM-PLS (Partial Least Square) as a data processing tool. The results of research that have been conducted show that supervisor support has a significant effect on employee engagement, the work environment has a significant effect on employee engagement, employee engagement has a significant effect on job performance, supervisor support has a significant effect on job performance, and work environment has a significant effect on job performance, supervisor support and work environment have a significant effect on job performance through employee engagement.